1994
DOI: 10.1002/micr.1920150606
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization and measurements of wound neovascularization: Application in microsurgery research

Abstract: Neovascularization or angiogenesis is an essential yet poorly understood component of the healing process. In wound healing research, there is a lack of models enabling quantitative and continuous measurements of wound neovascularization. The hairless mouse ear wound model permits quantitative measurements of wound epithelialization and neovascularization continuously throughout the healing process. On the ears of male homozygous (hr/hr) hairless mice, standardized circular full thickness dermal wounds are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…As these results suggested that the MEST-encoded protein may be involved in the process of neoangiogenesis that occurs during tumour formation, Mest expression was assessed during wound healing of murine skin. Although neoangiogenesis occurs during wound healing (Kjolseth et al, 1994;Thompson et al, 1991), Mest transcripts could not be detected in sections of skin undergoing healing (not shown).…”
Section: Mest/mest Expression In Choriocarcinoma Grown In Nude Micementioning
confidence: 57%
“…As these results suggested that the MEST-encoded protein may be involved in the process of neoangiogenesis that occurs during tumour formation, Mest expression was assessed during wound healing of murine skin. Although neoangiogenesis occurs during wound healing (Kjolseth et al, 1994;Thompson et al, 1991), Mest transcripts could not be detected in sections of skin undergoing healing (not shown).…”
Section: Mest/mest Expression In Choriocarcinoma Grown In Nude Micementioning
confidence: 57%
“…Consequently, the effects of many factors on angiogenesis still remain unknown. [6][7][8] The increase in total blood vessel length at 32% and 63% after fibroblast growth factor (FGF) and TGF-injections applied for 20 days indicates that FGF and TGF-assume the main role as the progenitor of endothelial cells in angiogenesis. 16,17 This study has demonstrated the epidermal growth factor increases the degree of healing in connective tissue but it does not affect angiogenesis, as previously assumed.…”
Section: Resultsmentioning
confidence: 98%
“…The ear of the homozygous hairless mouse measures about 13 mm 2 . The total thickness is approximately 300 µm with a central cartilage layer between two layers of skin [3,4,9,11,18,19]. All handling of the animals was performed under anesthesia (ketamine 50 mg/kg and xylazine hydrochloride 5 mg/kg i.p.).…”
Section: Animal Modelmentioning
confidence: 99%